Takeoff and Turbulence in Modernizing Peru - Julio F. Carrión (Latin American Research Review, 2019)
This essay reviews the following works: Peru: Elite Power and Political Capture. By John Crabtree and Francisco Durand. London: Zed Books (distributed by University of Chicago Press), 2017. Pp. viii + 206. $29.95 paperback. ISBN: 9781783609031.   Peru in Theory. Edited by Paulo Drinot. New York: Palgrave Macmillan, 2014. Pp. ix + 255. $105.00 hardcover. ISBN: 9781137455253.   Rethinking Community from Peru: The Political Philosophy of José María Arguedas. By Irina Alexandra Feldman. Pittsburgh: University of Pittsburgh Press, 2014. Pp. ix + 175. $29.95 paperback. ISBN: 9780822963073.   The Rarified Air of the Modern: Airplanes and Technological Modernity in the Andes. By Willie Hiatt. New York: Oxford University Press, 2016. Pp. vii + 215. $49.54 hardcover. ISBN: 9780190248901.   Andean Truths: Transitional Justice, Ethnicity, and Cultural Production in Post–Shining Path Peru. By Anne Lambright. Liverpool: Liverpool University Press, 2015. Pp. vii + 212. $120.00 hardcover. ISBN: 9781781382516.   Now Peru Is Mine: The Life and Times of a Campesino Activist. By Manuel Llamojha Mitma and Jaymie Patricia Heilman. Durham, NC: Duke University Press, 2016. Pp. ix + 229. $23.95 paperback. ISBN: 9780822362388.   Peru: Staying the Course of Economic Success. Edited by Alejandro Santos and Alejandro Werner. Washington, DC: International Monetary Fund, 2015. Pp. xv + 440. $40.00 ISBN: 9781513599748.